AlphaZero – What’s Missing? - Bratko, Ivan (Informatica, 2018)
In December 2017, the game playing program AlphaZero was reported to have learned in less than 24 hours to play each of the games of chess, Go and shogi better than any human, and better than any other existing specialised computer program for these games. This was achieved just by self-play, without access to any knowledge of these games other than the rules of the game. In this paper we consider some limitations to this spectacular success. The program was trained in well-defined and relatively small domains (admittedly with enormous combinatorial complexity) compared to many real world problems, and it was possible to generate large amounts of learning data through simulated games which is typically not possible in real life domains. When it comes to understanding the games played by AlphaZero, the program’s inability to explain its games and the knowledge acquired in human-understandable terms is a serious limitation.